Analysis of Factors Affecting Employee Performance In The Scope of PT Sugar Factory Sragen - Salsabilla Yusika Anjany; Zandra Dwanita Widodo; Atik Lusia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Performance is the result of work that has been produced by individual employees in terms of both quality and quantity in carrying out a task assigned to them. This study aims to analyze the influence of work discipline, work motivation, and work environment on the performance of employees at PT Sugar Factory Mojo Sragen, both partially and simultaneously. This study uses primary data and is quantitative in nature. The quality of the data in this study was tested for validity and reliability. The data collection methods used observation and questionnaires. The sample size was 71 people. Data analysis was performed using multiple linear regression. The results of the study indicate that work discipline, work motivation, and work environment partially have a significant effect on employee performance. Work discipline is the variable that has the most dominant effect on employee performance. Simultaneously, work discipline, work motivation, and work environment have a significant effect on employee performance with a significance value of 0.000, which is less than 0.05. The coefficient of determination (Adjusted R Square) value of 0.521 indicates that 52.1% of the variation in employee performance can be explained by work discipline, work motivation, and work environment, while the remaining 47.9% is influenced by other variables not examined in this study.